PEMBERDAYAAN UMKM MASYARAKAT DESA KALIPANG MELALUI PELATIHAN DAN PENGURUSAN PANGAN INDUSTRI RUMAH TANGGA (PIRT) - Nurul Akramiah; Yufenti Oktafiah; Ratna Pudyaningsih (JURNAL PENGABDIAN MANDIRI, 2024)
This service activity focuses on developing Micro, Small and Medium Enterprises (UMKM) in Kalipang Village, Grati District, Pasuruan Regency as a form of empowerment in improving community welfare. The problems that arise in Kalipang Village are that the community's potential in entrepreneurship is still lacking, so there needs to be motivation so that people have an entrepreneurial spirit. Assistance is given to UMKM that have the potential to develop, namely cassava tape and samiler crackers. The purpose of this activity is to educate or provide socialization and training to the village community, the socialization provided is about the importance of Home Industry Food Management (PIRT) and the management of trademark patent rights. The training provided is compiling simple financial reports or bookkeeping, innovation to existing products, and how to market products through social media and market places